Pyrene‐diaminomaleonitrile‐based fluorescent probe for the turn‐on detection and bioimaging of hypochlorite - Bingbing Yue; Ruida Shi; Huiwen Yang; Caifeng Ding; Haitao Yu; Yanyu Qi (Responsive Materials)
Abstract Hypochlorous acid (HClO), a key member of the reactive oxygen species, has an impact on both normal and abnormal functioning of a wide range of organisms. To deeply investigate the function of HClO in organisms and its impact on health status, there is an urgent need to develop efficient detection techniques in the biomedical field. Herein, a highly selective and sensitive hypochlorite fluorescent probe (Py‐DA) was designed and synthesized. Photophysical property tests and response behavior studies of Py‐DA showed high‐performance turn‐on detection of HClO/ClO−, including fast response, high sensitivity, excellent selectivity, and strong anti‐interference capabilities. Significantly, the emission intensity showed a good linear relationship with HClO/ClO− concentration in the range of 0–30.0 μM, and the detection limit was as low as 37.8 nM. In addition, convenient on‐site rapid (∼1 s) visual identification of aqueous HClO/ClO− was also realized via Py‐DA‐based paper strips. Furthermore, Py‐DA with good photo‐stability and low cytotoxicity has been successfully applied for HClO/ClO− imaging in human cervical cancer cells (HeLa). The results of this study provide new ideas for further investigation of the physiological and pathological effects of HClO.